Penerapan Layanan E-Commerce pada Laras Florist Kisaran - Wan Mariatul Kifti; Nasrun Marpaung (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2018)
In the current era of golabalisasi, promotional activities are very important to be able to market products / services to the general public, namely using a modern marketing concept known as e-Commerce system (online marketing). With e-Commerce system is expected, is expected to market services Laras Florist better. The research objective of applying e-commerce services in marketing Laras Florist services is expected to be achieved, namely (1) Designing a system that can perform analysis and data processing related to promotional activities. (2) Reach wider marketing and facilitate consumers to make ordering transactions easier. (3) Designing systems and software that can generate output relating to the promotion or marketing of services to the Florist Larry. (4) Comparing the effectiveness and effectiveness of information systems designed with the current system. The results of this study will be useful (1) Provide alternative system proposal to Laras Florist which later can be used to facilitate the work in promotional activities and sales services (2) From the existing system will be able to help Laras Florist in sales services flower board. Keyword: e-commerce